10 Marked differences in the pharmacokinetic and pharmacodynamic profiles of ticagrelor in patients undergoing treatment for ST elevation and non ST elevation myocardial infarction (stemi and nstemi). (June 2018) - Khan, Nazish; Amoah, Vincent; Cornes, Mike; Martins, Joe; Wrigley, Ben; Khogali, Saib; Nevill, Alan; Cotton, James
Abstract : Introduction: Ticagrelor, an orally administered, direct acting, reversible P2Y12 receptor inhibitor, provides faster onset and greater levels of platelet inhibition when compared to clopidogrel. Current data indicates a reduced antiplatelet effect in STEMI. We sought to determine the early pharmacokinetic (PK) and pharmacodynamic (PD) effect of ticagrelor loading doses administered to patients undergoing PCI for STEMI and NSTEMI. Methods: This is a single centre non-randomised study. P2Y12 naive patients presenting with STEMI or NSTEMI were considered for inclusion. All patients gave informed consent. Enrolled patients were administered a loading dose of aspirin 300 mg and ticagrelor 180 mg prior to PCI. Blood was sampled at 20 min, coronary balloon time, 1 hour and 4 hours after loading. PD results are expressed as P2Y12 reaction units (PRU) and were assessed using VerifyNow. A PRU>208 indicates a sub-optimal antiplatelet response. PK properties were assessed by measuring plasma concentration of ticagrelor parent compound (T-PC) and active metabolite (T-AM) using liquid chromatography in tandem with mass spectrometry. The lower limits of quantification of T-PC and its active metabolite, AR-C124910XX (T-AM) are 1 ng/ml and 2.5 ng/ml respectively. PRU and plasma concentrations over time were tested between the two groups using 2-way ANOVA. p<0.05 was considered significant. Results: 30 patients (15 STEMI/15 NSTEMI) were recruited. Baseline characteristics are described in Table 1. PD analysis: In STEMI patients high residual platelet reactivity is seen at 20 min following administration of ticagrelor 180 mg (256±13.1), an attenuated effect is also observed at 4 hours. However, in our NSTEMI patients, a marked and rapid antiplatelet effect is seen at all time points (figure 1). PK analysis: Low plasma concentrations of T-PC are observed in STEMI vs NSTEMI patients; (9.0±4.1) vs (22.8±10.3), p=0.225 and this trend continues until 4 hours. A similar trend is noted for T-AM concentrations (figure 2). Conclusion: Ticagrelor, in STEMI does not provide adequate P2Y12 inhibition at the point of reperfusion. In contrast platelet inhibition is significantly more rapid in patients with NSTEMI. Although a directly acting P2Y12 inhibitor that can exert an antiplatelet effect independent of metabolic biotransformation, ticagrelor is still reliant upon absorption via the gastrointestinal (GI) tract. The sub-therapeutic PRU and plasma concentrations of both T-PC and T-AM indicate that GI absorption is an important determinant of the onset of action and clinical efficacy of ticagrelor during the acute phase of a STEMI. GI absorption may be further impaired by co-administration of morphine. Modification of formulation e.g administration of chewed/orodispersible tablets or an intravenous agent (cangrelor) could help to overcome delayed GI absorption and provide adequate levels of platelet inhibition during the acute phase of presentation in STEMI patients.